Pelatihan Arduino kepada Remaja Mushola Ka’bah dengan Tema: “Santri Berdikari, Mandiri Teknologi” - Ikhwan Taufik; Hilmy, Fuad (Universitas Muhammadiyah Malang, 2023)
Al Iman is a prayer room with a unique shape like the Kaaba and have an ancient handwritten Al Qur'an by Syech Al Basyin in ancient times. Even though there are these privilege, it turns out that the time markers in the Al Iman prayer room are only limited to wall clocks. The problem is, Al Iman is relatively small, has just been built, and haven't enough cash to allocate to procuring digital prayer time markers (focus on completing construction). Meanwhile, local youth have a high learning spirit and the surrounding community looks very enthusiastic. This is proven by the existence of the Mushola Youth Association and the routine